EXPLAINING THE SPREAD OF TEMPORARY JOBS AND ITS IMPACT ON LABOR TURNOVER. (28th April 2016) - Cahuc, Pierre; Charlot, Olivier; Malherbet, Franck
Abstract : This article provides a simple model that explains the choice between permanent and temporary jobs. This model, which incorporates important features of actual employment protection legislations neglected by the economic literature so far, reproduces the main stylized facts about entries into permanent and temporary jobs observed in Continental European countries. We find that job protection has very small effects on total employment but induces large substitution of temporary jobs for permanent jobs, which significantly reduces aggregate production.